Active and dynamic infrared switching of VO2 (M) nanoparticle film on ITO glass. Issue 8 (27th January 2016) - Li, Ming; Wu, Hao; Zhong, Li; Wang, Hua; Luo, Yuanyuan; Li, Guanghai
Abstract : Stable and reversible infrared modulation of the VO2 (M) nanoparticle/ITO glass device upon an applied voltage. Abstract : An active and dynamic infrared switching film device was built via integrating VO2 (M) nanoparticles and the ITO glass substrate. The infrared optical transmittance of the device can be real-time manipulated by an applied voltage, overcoming the high T c limit of VO2 (M) and providing a new insight into the applications of transparent conductive electrodes in the thermochromic field.